2014
DOI: 10.1063/1.4891300
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cyanopolyyne anions in the interstellar medium: The possible role of permanent dipoles

Abstract: The possibility of attaching near-threshold electrons to N-terminated carbon chains, like those observed in the outer envelopes of carbon-rich stars, is examined via accurate quantum chemistry orbital structures evaluation and quantum scattering analysis of the corresponding extra-electron wavefunctions at meV energies. It is shown that the differences in the signs and sizes of the permanent dipole moments which exist for both the neutral and anionic species of the C(n)N series of molecules play a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…C 6 H, C 8 H or C 3 N), threshold effects could be important and the non-adiabatic couplings significantly larger. The study of the role of a permanent dipole moment in REA is out of the scope of the present study and has been discussed elsewhere [30,31]. Therefore, in the following development, we only consider the role of the number of degrees of freedom in the electron capture probability and discard the possible role of unusual threshold effects or vibrational Feshbach resonances.…”
Section: The Indirect Rea In Larger Moleculesmentioning
confidence: 99%
“…C 6 H, C 8 H or C 3 N), threshold effects could be important and the non-adiabatic couplings significantly larger. The study of the role of a permanent dipole moment in REA is out of the scope of the present study and has been discussed elsewhere [30,31]. Therefore, in the following development, we only consider the role of the number of degrees of freedom in the electron capture probability and discard the possible role of unusual threshold effects or vibrational Feshbach resonances.…”
Section: The Indirect Rea In Larger Moleculesmentioning
confidence: 99%
“…However, for all carbon chain anions observed in the ISM the potential energy surfaces of the neutral molecule and the anion are almost parallel to each other, which implies that the electron capture cross section is small. One possibility in the process of REA that was not considered in this approach, is the role of weakly-bound dipole states of molecules with large dipole moments, such as C 5 N. Recently, it was suggested [5][6][7] that the weakly-bound dipole states might enhance the REA cross section, although no quantitative predictions have yet been made. A dipole state with a rotationally or vibrationally excited molecular core appears as a resonance in the electronic continuum spectrum and, therefore, can in principle enhance the REA cross section, at least, in some energy domains.…”
mentioning
confidence: 99%
“…The discovery of several carbon chain anions, C n N − (n = 1, 3, 5) and C n H − (n = 4,6,8) in the ISM has prompted a discussion about mechanism of their formation in the ISM [4][5][6][7]. Well before their discovery, the formation of molecular anions in the ISM was theorized by Herbst [8], who suggested that the anions could be formed in the ISM by radiative electronic attachment (REA).…”
mentioning
confidence: 99%
“…[22] However, the collisional dynamics and atomic silicon bonding preferences [23][24][25][26] of SiCH are likely to retain the additional electron in much the same way that another known interstellar anion, CN 2 , is believed to form collisionally in the ISM. [27][28][29] Hence, the detection or even nondetection of SiCH 2 in the ISM will provide more details about how anions may form in these environments. Furthermore, no siliconterminated alkyne chain molecules have been detected in the ISM even though there exists much speculation that they should be present therein.…”
Section: Introductionmentioning
confidence: 99%